The 90% minimum effective concentration of ropivacaine for ultrasound‐guided interscalene brachial plexus block in children aged 1-10 years: A biased coin design up‐and‐down sequential allocation trial - Li Yang; Fei Yang; Yaqiong Tian; Ling Liu; Shangyingying Li; Tauseef Ahmad; Yuan Shi; Shengfen Tu (Wiley, 2024)
Abstract Ropivacaine is a commonly used local anesthetic for brachial plexus blocks in children, but the minimum effective dose of ropivacaine for interscalene brachial plexus blocks has not been reported. The aim of this study was to determine the 90% minimum effective concentration (MEC90) of ropivacaine for an ultrasound‐guided interscalene brachial plexus block (ISB). A total of 155 patients, aged from 1 to 10 years, underwent unilateral surgical procedures on areas of the upper extremity not innervated by the ulnar nerve. The biased coin design up‐and‐down sequential method (BCD‐UMD) was used to determine the MEC90 of ropivacaine for ultrasound‐guided ISB. In our study, the initial concentration of ropivacaine was 0.07% in the toddler group and 0.09% in the preschool and school‐age groups. During the trial, the concentration of ropivacaine for each subsequent patient was determined by the blocking effect of the previous patient. In case of failure, the concentration for the next patient was increased by 0.01%. Otherwise, the concentration was either decreased by 0.01%, with a probability of 0.11, or kept the same, with a probability of 0.89. Overall, the MEC90 of ropivacaine was 0.104% (95% confidence interval (CI), 0.070%-0.106%) in the toddler group, 0.114% (95% CI, 0.090%-0.117%) in the preschool group, and 0.133% (95% CI, 0.099%-0.136%) in the school‐age group. No adverse events occurred. Our study showed that lower concentrations of ropivacaine could provide effective nerve blocks and reduce the risk of local anesthetics.